Analysis of Fixed Asset Treatment at PT Hexindo Adiperkasa Tbk, Pekanbaru Branch - Azani, Nazwira; Ruslan, Marsya Aliya Dini; Hayyu, Dinda Amanah; Rodiah, Siti (Research in Accounting Journal (RAJ), 2024)
Fixed assets are one of the essential requirements a company must possess to support its operational activities. The purpose of this study is to examine the accounting treatment of fixed assets applied by PT Hexindo Adiperkasa Tbk, Pekanbaru Branch, in relation to the Indonesian Financial Accounting Standards Statement (PSAK) No. 16. This includes the acquisition of fixed assets, depreciation, disposal and retirement, as well as the presentation and disclosure of fixed assets in financial statements. The research method used is descriptive with a qualitative approach. The data collected consists of both primary and secondary data from the company, using interviews and documentation as data collection techniques. Based on the results of this study, it was found that the company’s accounting policies regarding fixed asset treatment are in accordance with PSAK No. 16.